2008
DOI: 10.1121/1.2999341
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between native allophonic experience with vowel duration and perception of the English tense/lax vowel contrast by Spanish and Russian listeners

Abstract: Two studies explored the role of native language use of an acoustic cue, vowel duration, in both native and non-native contexts in order to test the hypothesis that non-native listeners' reliance on vowel duration instead of vowel quality to distinguish the English tense/lax vowel contrast could be explained by the role of duration as a cue in native phonological contrasts. In the first experiment, native Russian, Spanish, and American English listeners identified stimuli from a beat/bit continuum varying in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 44 publications
4
84
2
Order By: Relevance
“…Previous research has demonstrated that allophonic experience from learners' native language improves both perception of non-native contrasts as well as their learning. (Best and Strange 1992;Halle et al 1999;Jamieson and Moroson 1986;Jenkins and Yeni-Komshian 1995;Kondaurova and Francis 2008;McAllister et al 2002;McClaskey et al 1983;Pisoni et al 1982;Pruitt et al 2006). The current results suggest that such experience also contributes to imitation.…”
Section: Does the Type Of A Sequence -Same Place Of Articulation Vs supporting
confidence: 51%
“…Previous research has demonstrated that allophonic experience from learners' native language improves both perception of non-native contrasts as well as their learning. (Best and Strange 1992;Halle et al 1999;Jamieson and Moroson 1986;Jenkins and Yeni-Komshian 1995;Kondaurova and Francis 2008;McAllister et al 2002;McClaskey et al 1983;Pisoni et al 1982;Pruitt et al 2006). The current results suggest that such experience also contributes to imitation.…”
Section: Does the Type Of A Sequence -Same Place Of Articulation Vs supporting
confidence: 51%
“…They also support the prediction that complete acquisition of L2 contrasts is difficult for speakers of a native language which does not rely on the relevant acoustic cues for phonemic discrimination. These results support previous work claiming the primacy of duration as a cue to vowel identity (over vowel quality) by non-native speakers (Kondaurova & Francis 2008, Flege 2007). …”
Section: Discussionsupporting
confidence: 82%
“…Kondaurova and Francis, 2008), to obtain standardized logit coefficients, or b weights, as a measure of the strength of the contribution of each variable (VOT and onset f0) to the category ([b] or [p]) as shown in Fig. 1(b).…”
Section: Analysis and Resultsmentioning
confidence: 99%